Fish Diversity of Tamor River and its Major Tributaries of Eastern Himalayan Region of Nepal - Shrestha, Jiwan; Singh, Dharani Man; Saund, Tej Bahadur (Nepal Journal of Science and Technology, 2010)
A total of 30 fish species from different sampling stations were recorded. Psilorhynchoides pseudecheneis, endemic fish of Nepal, was recorded from all seven stations, which can be considered as a common species of the study area. Recorded fish species were classified into two orders and five families. Order Cypriniformes comprised of four families: Cyprinidae, Cobitidae, Balitoridae and Psilorhynchidae with 26 species while order Siluriformes comprised of one family: Sisoridae and four species. Cyprinidae, Cobitidae, Balitoridae and Psilorhynchidae comprised 61%, 13%, 10% and 3% respectively while Sisoridae comprised of 13% fish species. The common species of Tamor river were Psilorhynchoides pseudecheneis followed by Barilius shacra, Barilius bendelisis, Barilius barila, Schizothoraichthys labiatus, Schizothoraichthys progastus, Schizothorax richardsonii, Neolissochilus hexagonolepis and Garra annandalei. Most of the species collected during the field survey have economic value as food, medicinal, recreation and aesthetic purposes. The water quality parameters i.e. air temperature (22-26.3°C), water temperature (16.0-19.0°C), DO (9.7-10 ppm), pH (7.3-7.5), alkalinity (17.1 mg/l), total hardness (28.5-34.2 mg/l), CO2 (5 mg/l) and conductivity (37.7-56.7 μs/cm) were found within the suitable range for cold water fishes. Key words: Eastern Himalayas region; Tamor river; Fish diversity; Fish dominancy; Physico-chemical parameters DOI: 10.3126/njst.v10i0.2964 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 219-223